Audit Kepatuhan terhadap Regulasi Anti Money Laundering / Countering the Financing of Terrorism (AML/CFT) pada Perusahaan Fintech di Indonesia: Tinjauan Literatur 2020–2025 - Adam Desvian Muhidin; Trinandari Prasetya Nugrahanti (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The rapid expansion of financial technology (fintech) in Indonesia has created substantial challenges for the effective implementation of Anti-Money Laundering and Countering the Financing of Terrorism (AML/CFT) compliance. This study aims to systematically examine key issues, regulatory practices, and the effectiveness of AML/CFT implementation within the Indonesian fintech sector. The research employs a qualitative approach using a Systematic Literature Review (SLR) method. Data were collected through document analysis of 15 scholarly articles published between 2020 and 2025, sourced from nationally accredited Sinta-indexed journals and reputable international journals. Literature selection was conducted using predefined inclusion and exclusion criteria, focusing on relevance, journal quality, and alignment with the Indonesian regulatory context. The data analysis technique applied was thematic and comparative analysis, categorizing findings into compliance auditing, AML/CFT program implementation, risk management practices, and regulatory supervision. The results indicate that AML/CFT compliance in Indonesian fintech remains constrained by inadequate technological infrastructure, limited skilled human resources, weak inter-agency coordination among the Financial Services Authority (OJK), Bank Indonesia, and the Financial Transaction Reports and Analysis Center (PPATK), as well as the prevalence of illegal fintech operators. Preventive mechanisms such as Know Your Customer (KYC), Customer Due Diligence (CDD), and Enhanced Due Diligence (EDD) are essential but require significant technological investment and continuous capacity building. This study recommends strengthening regulatory harmonization, enhancing audit and compliance functions, promoting RegTech and SupTech adoption, and expanding future empirical research across fintech business models.